Avaliação dos efeitos do consumo de pasta de gergelim (Sesamum indicum L.) no estado fisiológico de atletas de futebol - Barbosa, Carlos Vinícius da Silva (2013)
The strenuous exercise when performed with unbalanced diet and recovery period of the athlete can promote an undesirable state of chronic inflammation and generation of reactive oxygen species (ROS). Those compounds can degrade muscle proteins and contribute to the signs and symptoms of muscle injuries. In recent years, those foods have been tested for their ability to attenuate the deleterious effects in athletes undergoing intense days of training and competition. In this context, sesame (Sesamum indicum L.) stands out for presenting a high nutritional value and recognized antioxidant and anti-inflammatory properties. Considering these aspects, the present study had as its goal to evaluate the effects of the sesame paste consumption (S. indicum L.) on oxidative stress, inflammatory markers and muscle injuries in soccer players. Therefore, a randomized and placebo controlled study was conducted with 19 male soccer athletes, teenagers, with age about 16 years. The sesame paste has been prepared with an addition of 30% of honey from Apis mellifera. The participants were randomly assigned to consume 40 g / d sesame paste or placebo during 28 days of normal training. Before and after intervention were performed anthropometric measurements, functional exams and dosing blood creatine kinase (CK), lactate dehydrogenase (LDH), malondialdehyde (MDA) and high-sensitivity c-reactive protein (hs-CRP) and during a four-week study was performed an evaluation of athletes dietary intake. Biochemical analyzes indicated a physiological unbalanced state of the athletes at the beginning of the experimental procedure. The intake of sesame paste resulted in decreased lipid peroxidation (p=0,002), reduced serum levels of hs-CRP (p=0,010) and LDH (p=0,001), accompanied by an improvement in the aerobic power (p=0.011) and top speed (p=0.005). On the other hand, it was not observed any change of these variables in the placebo group. For anthropometric variables, running speed at the lactate threshold and CK, there were no differences observed in the groups that received sesame paste and placebo after the intervention period. The current study results suggest that the consumption of sesame paste represents an important nutritional strategy by its ability to reduce the inflammatory status, oxidative stress and cause repair of muscle tissue, increasing the physical performance of soccer players, particularly in soccer players previously worn.